Por uma “modernização tradicionalista”: o projeto político conservador na Colômbia de La Regeneración (Século XIX): For a “traditionalist modernization”: the conservative political project in Colombia by La Regeneración (19th century) (Revista de História da UEG (REVHIST), 2021)
This work proposes to analyze the period of Colombian history known as La Regeneración, chronologically situated in the late decades of the eighties. We intend to study the political and cultural project of the conservative elites that make up the regenerating governments, whose main representative was the president and intellectual Rafael Nuñez. The primary objective of the La Regeneración project was to promote traditionalist modernization in Colombia, characterized by rejecting the basic aspects of Western modernity - such as individual freedoms and rights - and incorporating certain modernizing elements on the economic and material plane - such as state strengthening, control of the caudillos and the modernization of state institutions. Conservatives had the Catholic Church as their main ally. In anticipation, we can say that the Colombian regenerative project was not anomalous or anachronistic in comparison with its Latin American neighbors, but was based on a speech that called for the reconstitution of the country.Keywords: History of Colombia. La Regeneración. Latin America.